Ethnopedagogical Study: Educational Values Depicted in Tumpek Wariga - Eka Suarmika, P; Syarifah, M (KnE Social Sciences, 2019)
This article aims to explore the educational values based on the local wisdom of Balinese people in carrying out the ritual Tumpek Wariga. This research is an ethnographic research. Data collected in this study were conducted with observation, interview, and literature study. The subjects for the interview include Hindu community leaders, religious leaders and the people of Bali. The analysis of data involves interpretation of the meanings and functions of Tumpek Wariga and mainly takes the form of verbal descriptions and explanations. There are some educational values in the sacred Tumpek Wariga Day:1) the value of trust and confidence in God that created man and all its contents; 2) teaches us to develop thinking skills by using contextual local culture; 3) teaches us to always respect the environment, others and ourselves and believe in the omnipotent God; and 4) Tumpek Wariga provides cultural significance in education. Keywords: ethnopedagogy, local wisdom, education, Tumpek Wariga.